The Challenges and Solutions of Cybersecurity Among Malaysian Companies - Puteri Fadzline, Muhamad Tamyez (IGI Global, 2019)
The objective of this chapter is to analyze the challenges faced by Malaysian companies in cybersecurity and to determine solution for Malaysian companies to overcome challenges in cybersecurity. The data were collected from the expert people in cybersecurity fields using interview sessions. The finding confirmed that the awareness and budget are very important in other to implement the element of cybersecurity in the company. Cybersecurity is good and desired as a protection for an organization in developing strategic planning to gain more profitability and increase the productivity of goods and services. This research will be beneficial for the organization because it will provide the solution for the company to overcome the cybersecurity issues. From this research, an organization can have potential to enhance competitiveness and understand the problem occur, then do the improvement by implementing cybersecurity.